LOS ESTADOS DE EXCEPCIÓN EN EL ORDENAMIENTO JURÍDICO COSTARRICENSE - Méndez, Juan C. (2014)
States of emergency have legal andpractical scopes that may vary inevery country. However, there iswide international doctrine and jurisprudencethat allows us to conceptualizea state of emergency asestablishments of temporary or provisionalnature intended to overcomeextraordinary crises and ensure thereturn to constitutional normality, always following parameters ofproportionality, timeliness, amongother elements.This article reviews the features andmodalities of state of emergencythat exists in Costa Rican, whichare adopted in accordance with thenature of the emergency or crisis,caused by natural events or by militaryactivities.